Meet and eat, an interdisciplinary group intervention for patients with myotonic dystrophy about healthy nutrition, meal preparation, and consumption: a feasibility study. Issue 11 (21st May 2020) - van Hees, Suzanne G. M.; Knuijt, Simone; Dicke, Heleen; Groothuis, Jan T.; Raaphorst, Joost; Satink, Ton; Cup, Edith H. C.
Abstract: Purpose: To develop and evaluate an interdisciplinary group intervention for patients with myotonic dystrophy regarding healthy nutrition, meal preparation, and consumption, called Meet and Eat. Materials and methods: A design-based approach was used, exploring experiences and needs of patients with myotonic dystrophy and their next of kin. This resulted in a 4-week interdisciplinary outpatient group intervention to increase awareness and change behavior. In a mixed-method feasibility study this intervention was evaluated with participants and facilitators. Results: Participants reported on social impact of difficulties with eating and drinking (speaking, swallowing, and social embarrassment) and a variety of complaints affecting meal preparation and consumption. Patients and family members expressed the wish to learn from others. After delivery of the intervention, self-reported outcome measures demonstrated improvement on eating and drinking issues in daily life. The qualitative evaluation showed increased awareness and appreciation of the following design principles: peer support, multidisciplinary approach, active involvement of patient with myotonic dystrophy and their next of kin by using personal goals and motivational interviewing. Conclusion: Participation in Meet and Eat seemed to increase insight in patients' condition and ways of management. However, a longer self-management life style program is recommended to change behavior. Implications for rehabilitation: Patients with myotonic dystrophy experience physical, cognitive and psychosocial problems to manage healthy nutrition, meal preparation, and consumption; This multidisciplinary group intervention Meet and Eat in patients with myotonic dystrophy appears to be feasible and seems to result in increased insight and management strategies; Peer support, multidisciplinary approach, personal goals, and involvement of family were key factors; To change eating and drinking behavior, a 4-week intervention is too short.